Examinations of ascites from prophylactic drains can predict intra‐abdominal infections after living donor liver transplantation. (8th July 2015) - Sanada, Yukihiro; Kawano, Youichi; Urahashi, Taizen; Ihara, Yoshiyuki; Wakiya, Taiichi; Okada, Noriki; Yamada, Naoya; Hirata, Yuta; Tashiro, Masahisa; Mizuta, Koichi
Abstract Studies suggest that prophylactic intra‐abdominal drains are unnecessary for cadaveric liver transplantation using whole liver grafts because there is no benefit from drainage. However, no studies have investigated on the necessity of prophylactic drains after LDLT using split‐liver grafts or reduced‐liver grafts, which may present a high risk of post‐transplant intra‐abdominal infections. This retrospective study investigated whether the ascitic data on POD 5 after LDLT can predict intra‐abdominal infections and on the post‐transplant management of prophylactic drains. Between March 2008 and March 2013, 90 LDLTs were performed. We assessed the number of ascitic cells, biochemical examinations, and cultivation tests at POD1 and POD5. The incidence rates of post‐transplant intra‐abdominal infections were 24.4%. The multivariate analysis showed that left lobe and S2 monosegment grafts were a significant risk factor for intra‐abdominal infections (p = 0.006). The patients with intra‐abdominal infections had significantly higher acsitic LDH levels and the positive rate of ascitic culture at POD5 in comparison with patients without infections (p < 0.001 and p = 0.014, respectively). LDLT using left lobe and S2 monosegment grafts yields a high risk for post‐transplant intra‐abdominal infections, and ascitic LDH and cultivation tests at POD5 via prophylactic drains can predict intra‐abdominal infections.